HUBUNGAN KEBIASAAN LAMA DUDUK TERHADAP PROSES TERBENTUKNYA KRISTAL URIN PADA PENJAHIT DI WILAYAH KOTA BENGKULU - Farizal, Jon (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
Background: Urine crystals are conditions in which the formation of stones in the outlet of the urine can be in the kidneys, ureters, bladder and urethra. The incidence of urinary tract stones (BSK) is more prevalent in people who sit in many jobs such as convection workers (tailors), because it interferes with the body's metabolism process and will cause bone loss calcium bleeding, will further spur the formation of urine crystals that will lead to the emergence of urinary tract stones. The purpose of this study is to know whether there is a relationship between the old habit of sitting on the process of formation of urine crystals at tailors in the city of Bengkulu Method: Using a cross sectional design with a sample of 30 respondents. The morning urine of the respondent is examined microscopically by the presence or absence of urine crystals found. Then the data is analyzed by using spearman correlation. Result: Long habits seated at tailors in bengkulu city area in 2017 with a sample of 30 samples known mean habits of seats sat tail mean is 8 hours and with median value of 7.94 hours, a minimum value of 7 hours and a maximum value of 10 hours. The result of statistic by using spearman test result p = 0,10 (p> 0,05) so there is no relation between old habit of sitting with process of urine crystals forming at tailor in city region Bengkulu Conclusion: There is no relation between old habit of sitting to process of crystal formation urine on tailors in the city area of Bengkulu